Devising a methodology for assessing seasonal thermal energy generation by a combined heat source - Pohosov, Oleksandr; Pasichnyk, Pavlo; Kulinko, Yevhen; Koziachyna, Bohdan; Melnychenko, Olexandr; Osypov, Valentyn (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is the process of calculating the distribution of heat generation and energy consumption by heat sources. The task addressed was estimating the seasonal heat generation by a combined heat source with an air heat pump. A methodology for quantifying the seasonal heat generation and energy consumption by sources as part of a combined heat source with an air heat pump has been devised. This methodology makes it possible to take into account different bivalent operation schemes, variable mode of the heating system, and different electricity tariffs. The ability to take these factors into account increases the accuracy of the results but also increases the complexity of the calculation process. In order to automate the calculation using the devised methodology, an algorithm was built, and an example of its implementation was demonstrated. The results show that the distribution of seasonal heat generation largely depends on the values of the bivalent point temperature and the heat pump shutdown temperature. In addition, they demonstrate the dependence of the calculated amount of heat consumed during the heating period and the distribution of its generation between sources on the number of the last heating periods taken into account. With a decrease in the number of past heating periods taken into account, the amount of heat consumed per season gradually decreases and the share covered by the heat pump increases. This indicates a gradual decrease in the duration of low temperatures in winter and proves the importance of relevance of the climatic data used for analysis. The methodology devised in this study makes it possible to determine the appropriate ratio of thermal power of heat sources in a combination and increases the accuracy of calculating the payback period of equipment